EDUCATIONAL MANAGEMENT: SIGNIFICANT REFLECTIONS - Boni, Cinara; Zancan, Sinara; Piccoli Diehl, Rosicler; Larissa da Silva Flores, Juliane; Raquel Faccin, Tânia; Possa Moreschi, Margarida; Scalcon dos Santos de Lima, Marta (Revista Gênero e Interdisciplinaridade, 2023)
Educational Management is based on democratic principles and is focused on the development and quality of teaching, allowing people to recognize the importance of collective and conscious participation in decisions involving collective interest. This idea envisages the realization of Educational Management, where everyone, in addition to overcoming limitations, can share the responsibilities of teamwork. Society is increasingly demanding to have a quality education, which means that all segments are always looking to improve the structures, the qualification of the teaching staff and thus have a better education. This requires responsibility and organization of all sectors of a school, it is necessary to focus on the processes that provide a safe and effective constructive teaching environment for the entire school environment. For educational management to have a good development, everyone needs to feel involved, from the administrative to the pedagogical sector, where managers must optimize activities and increase the efficiency of teaching within the educational institution.